PENGARUH PROBIOTIK TERHADAP KOLESTEROL DARAH PADA AYAM PETELUR (LAYER) (Effect of Probiotik on Blood Cholesterol in Laying Hens) - Sumardi Sumardi; Sutyarso Sutyarso; Gregorius Nugroho Susanto; Tintin Kurtini; Madi Hartono; Rr. Etty Puspitaningsih N.W. (Universitas Syiah Kuala, 2016)
The aim of this research was to find out the effect of probiotic on blood cholesterol in laying hens. Materials used were laying hens (Isa Brown strain) 43 weeks old and ration using probiotics. This research was conducted by using completely randomized design (CRD). The advanced research was done with testing the local probiotic with various concentration treatment, they are P0 (ration without probiotic), P1 (ration + 1% local probiotic), P2 (ration + 2% local probiotic), and P3 (ration + 3% local probiotic) with 5 time repetitions and in every repetitions consists of 2 chicken. Variables that were observed in the advance research were laying hens’s blood cholesterol that consists of total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), triglycerides, and total leucocyte. The level of total cholesterol on P0, P1, P2, and P3 were 129.00±38.26, 116.00± 26.53, 121.00±33.72, and 137.00±52.53 mg/dL (P0.05) respectively; the HDL level were 50.60±16.47, 35.80±11.28, 59.40±19.74; 56.80±30.56 mg/dL (P0.05); the LDL level were 100.20±49.53, 39.20±17.14, 104.60±51.23, and 96.80±66.22 mg/dL (P0.05), respectively; the trigycerides level were 862.00±355.5, 533.00±146.1, 829.00±242.6, and 810.00±304 mg/dL (P0.05), respectively; and leucocyte count were 22.00±1.72, 21.00±3.79, 31.00±3.99, and 34.00±3.55 x103 mm3 (P0.01), respectively. In conclusion, the administrtion of local probiotic do not effect the blood cholesterol of layer chicken.